Endothelium-derived hyperpolarizing factor (EDHF) in rat mesenteric artery. - Burnette, Ethan Williams. (University of Ottawa (Canada), 2001)
The endothelium, a critical modulator of vascular resistance and blood pressure, can release at least three factors that relax vascular smooth muscle, including nitric oxide (NO), prostacyclin (prostaglandin I2, PGI 2), and endothelium-derived hyperpolarizing factor (EDHF). EDHF-induced relaxation is correlated with a strong hyperpolarization and may activate vascular smooth muscle cell (VSMC) K-channels. The research presented studied ACh-induced EDHF release from rat tail artery (TA) and superior mesenteric artery (SMA). Calcium-activated potassium (KCa) channels in the rat mesenteric resistance artery (MRA), putative targets of EDHF, were characterized. ACh-induced EDHF release from rat TA or SMA hyperpolarized target single TA VSMCs current-clamped with the nystatin perforated patch technique. In the absence of donor tissue, ACh induced depolarization. TA and MRA VSMCs were patch clamped in the whole-cell configuration and macroscopic K-currents were elicited by depolarizing pulses. Calcium-activated (KCa) and voltage-dependent (Kdr) potassium currents were observed in both TA and MRA VSMCs. Apamin (300 nM) significantly inhibited MRA (79% of control at +50 mV) but not TA whole-cell KCa Current. Iberiotoxin (IbTX) or charybdotoxin (ChTX) (150 nM) abolished KCa current in TA and MRA VSMCs. Single rat MRA VSMCs were patch clamped using the inside-out technique. Four KCa channels were observed and named: BK. IK, SK, and miniK (big, intermediate, small, and mini KCa channels). In symmetrical potassium (150 mM), the single channel conductances were linear (BK, 197: IK, 94; SK, 50; miniK, 31 pS) and similar to those observed in rat TA. ChTX (150 nM) completely blocked the BK, IK, and miniK channels, and dramatically inhibited the SK channel (inside-out. +40 mV, [Ca2+] i = 500 nM). IbTX (150 nM) completely blocked all MRA KCa channels. 4-AP (2 mM) completely blocked the BK and IK channels, partially blocked the SK channel, and dramatically inhibited the miniK channel. Apamin (300 nM) selectively blocked the BK channel. (Abstract shortened by UMI.)
Keywords: Biology, Molecular.